A new flavanone sulfonate and other phenolic compounds from Fumana montana. (October 2019) - Laraoui, Habiba; Haba, Hamada; Long, Christophe; Benkhaled, Mohammed
Abstract: The phytochemical study of ethyl acetate and n -butanol extracts of Fumana montana Pomel yielded a new flavanone sulfonate named naringenin-8-sulfonate (1 ), in addition to nine known compounds including two flavonols; tellimoside (2 ) and isoquercetrin (3 ), two flavanols; (−)-gallocatechin (4 ) and (−)-epigallocatechin (5 ), one benzophenone glucoside; iriflophenone-2- O -β-glucoside (6 ), one phenolic glucoside; (−)-rhododendrin (7 ) and three benzoic acid derivatives; p-hydroxybenzoic acid (8 ), gallic acid (9 ) and methyl gallate (10 ). It should be noted that this is the first report of compounds (2 ) and (6 ) in Cistaceae family. The structures of the isolated compounds were determined by comprehensive 1D and 2D NMR analysis, mass spectrometry, IR and by comparison with literature data. Graphical abstract: Image 1 Highlights: We study the chemical composition of Fumana montana Pomel. Ten phenolic compounds are isolated and identified. Sulfate flavanone is new. The study confirms the polyphenolic character of Fumana species.